اثر التمرين الموزع والمكثف بالاسلوب الثابت والمتغير بطريقه التعلم الاتعاوني في تعلم مهارة دقه التهديف بكرة القدم - مصطفى صبحي احمد (الرياضة المعاصرة, 2015)
The present project aims at studying the following : 1- Explore the effect of cooperative learning in style practice distribute constant , distribute varied , massed constant , and massed varied in teaching accuracy goalling skill in football The study has been conducted on a sample of (32) students intermediate youth school which divided in to two groups ( distribute practice group and massed practice group ) each consist of (16) students each group is divided in to two parts ( part of constant style and part of varied style ). Each part contains eight primary for each of four parts more over equivalence has been achieved for both groups to be learn accuracy goalling skill in football . these were taken as pre – tests . A special teaching course for the studying material has been designed according to traditional styles for the period of carrying out the project from ) 23 / 2 to 30 / 4 / 2014) past – tests have been conducted after completing the learning skill of both groups . the data has been analyzed and processed using bag system (SPSS) and use the convenient acts to taking consequences , and the most important conclusions can be derived from the study 1- There is a primacy for distribute varied over all groups in learning accuracy goaling skill in football . 2- There is a primacy for distribute constant over both groups (massed constant and massed varied ) in learning accuracy goalling in football .